Racial-Ethnic Identity and Academic Self-Efficacy of Indigenous Australian Students Studying on Scholarships at Independent Australian Boarding Schools—A Systematic Quantitative Literature Review. Issue 3 (3rd July 2019) - Parsons, Alan
ABSTRACT: By 2016, 3, 369 places in Australian boarding schools were held by Aboriginal and Torres Strait Islander students. Of these, nearly 2, 350 Indigenous students attended independent boarding schools, many on scholarship. Despite these numbers and the historical inequalities and assimilationist policies of the past, there is very limited research on the impact of the independent boarding school environment on the racial-ethnic identity formation and academic self-efficacy of these students. Using the systematic quantitative literature review method, from an initial search result of 204 papers, 66 papers were identified in peer-reviewed journals that explore some aspect of racial-ethnic identity, academic self-efficacy, or the boarding experiences of Indigenous students. Of these papers, only five qualitative studies make mention of aspects of identity and self-efficacy of Aboriginal and Torres Strait Islander students enrolled in independent boarding schools, although no exploration was made of these characteristics. This paper identifies research priorities that will enhance understanding of the consequences of Indigenous scholarship programs on the racial-ethnic identity and academic self-efficacy of these students.